Quantitative determination of polysulfide in albumins, plasma proteins and biological fluid samples using a novel combined assays approach - Ikeda, M.; Ishima, Y.; Shibata, A.; Chuang, Victor; Sawa, T.; Ihara, H.; Watanabe, H.; Xian, M.; Ouchi, Y.; Shimizu, T.; Ando, H.; Ukawa, M.; et al. (Elsevier, 2017)
Hydrogen sulfide (H2S) signaling involves polysulfide (RSSnSR') formation on various proteins. However, the current lack of sensitive polysulfide detection assays poses methodological challenges for understanding sulfane sulfur homeostasis and signaling. We developed a novel combined assay by modifying Sulfide Antioxidant Buffer (SAOB) to produce an “Elimination Method of Sulfide from Polysulfide” (EMSP) treatment solution that liberates sulfide, followed with methylene blue (MB) sulfide detection assay. The combined EMSP-MB sulfide detection assay performed on low molecular weight sulfur species showed that sulfide was produced from trisulfide compounds such as glutathione trisulfide and diallyl trisulfide, but not from the thiol compounds such as cysteine, cystine and glutathione. In the case of plasma proteins, this novel combined detection assay revealed that approximately 14.7, 1.7, 3.9, 3.7 sulfide mol/mol released from human serum albumin, a1-anti-trypsin, a1-acid glycoprotein and ovalbumin, respectively, suggesting that serum albumin is a major pool of polysulfide in human blood circulation. Taken together with the results of albumins of different species, the liberated sulfide has a good correlation with cysteine instead of methionine, indicating the site of incorporation of polysulfide is cysteine. With this novel sulfide detention assay, approximately 8,000, 120 and 1100 µM of polysulfide concentrations was quantitated in human healthy plasma, saliva and tear, respectively. Our promising polysulfide specific detection assay can be a very important tool because quantitative determination of polysulfide sheds light on the functional consequence of protein-bound cysteine polysulfide and expands the research area of reactive oxygen to reactive polysulfide species.